The road to 2024 olympic gold medal: a case report of three elite beach volleyball players - Medeiros, A.; de Jesus, K.; Neto, F. O.; Palermo, L.; Messias, G. (ISBS Proceedings Archive (Michigan), 2022)
The anthropometrics, limbs maximum isometric force and jump performance in beach-volleyball players were described. Three female elite beach volleyball players selected to participate in the 2022 World Championships Circuit were recruited to participate in the study. Body composition, squat, supine, and rowing isometric maximal force, and power test, squat, and countermovement jumps were measured. Body fat percentage varied between 13 and 24.2%. Squat, supine and rowing isometric force (N) presented median (M) and interquartile ranges (IQR) of 145 (128, 186.6), 40 (33, 66.75) and 65.2 (57.6, 76,6). The height (cm), absolute (W) and relative power (W/kg) M and IQR range values were 32.55 (27.32, 35.10), 32.69 (31.50, 34.69) and 44.18 (40.65, 46.30). Findings can guide morphological and physical training for elite players.